Anti-theft car seat design (electronic/control) - Mahfuzah, Mohd Nasir (2009)
The purpose of this project is to investigate the application of motor control system that suit to the new movement mechanism of driver car seat. The objective of this project is to design control circuit and integrate electric and electronic devices to the mechanism of the anti theft car seat. This Project involved of Infrared Transmitter circuit and Infrared Receiver circuit of 12 volts DC Motor. The motor will rotate bidirectional due the command of code that has been installing in the microcontroller. The coding inside the microcontroller has been programmed by using the Visual Basic software. PICAXE14M microcontroller has been selected for the control circuit because it is very appropriate with this control circuit system and PICAXE14M also good for the motor controller. 12 volt of DC motor is connected to control a new mechanism of seat movement which is rack and pinion gearing system and Internal gearing system. The rack and pinion gearing system is the system for the movement forward and backward of the car seat whiles the internal gearing system for bend the backrest of the seat down and up. Both of this mechanism involved of same types of gearing profiles. The types of gear used in this mechanism are the spur gear. A pair of spur gear is mesh together. One essential for correct meshing of the gears is that the size of the teeth on the pinion is the same as the size of teeth on the wheel. The pinion is the smallest gear and the larger gear is called the gear wheel .The 10 teeth of the smaller pinion and the 20 teeth of the wheel lay to the parallel axes. The module types used in this gearing system are 1 module. Module is the unit of size that indicates how big or small gear is. It is the ratio of the reference diameter of the gear divided by the number of teeth. The 20 teeth of gear wheel are coupled together with the 40 teeth of gear as the output gear. The purpose used the 40 teeth of output gear because of the gear reduction. The output speed of a DC motor is usually too fast for normal used. Most DC motors at normal operating voltages spin at high RPM or revolutions per minute so it is really necessary to reduce the rate at the wheel spins to suit the normal movement of seat. The gear reduction also can increase the torque of the motor to the output gear. This output gear is attached and mesh together with a rack and the internal gear. A rack is a rectangular prism with gear teeth machined along one side. The internal gear is hollow. The profile and teeth shape is similar as of external gear except that the internal gear had different addendum and dedendum values modified to prevent interference meshes. They are used in planetary gears to produce large reduction ratios. The gear ratio is the relationship between the numbers of teeth on two gears that are meshed. In this project all the gear ratio is 1:2.The simulation of the gearing system done by using the SolidWorks software. Solidworks is a 3D mechanical CAD or computer aided design program that runs on Microsoft window. The obtained result in this project also considered whether it is suitable to make the car seat as the new anti theft device for the future. All the suggestion and recommendation to improve this project had been written in the last chapter.